2019
DOI: 10.1021/acscentsci.8b00850
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Angiogenesis in Oxidative Diabetic Wound Microenvironment Using a Nanozyme-Reinforced Self-Protecting Hydrogel

Abstract: Impaired diabetic wound healing represents a devastating and rapidly growing clinical problem associated with high morbidity, mortality, and recurrence rates. Engineering therapeutic angiogenesis in the wounded tissue is critical for successful wound healing. However, stimulating functional angiogenesis of the diabetic wound remains a great challenge, due to the oxidative damage and denaturation of bio-macromolecule-based angiogenic agents in the oxidative diabetic wound microenvironment. Here, we present a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
173
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(175 citation statements)
references
References 42 publications
2
173
0
Order By: Relevance
“…The design of this drug delivery system ensured that antagomiR-26a had direct contact with the ceria nanozymes, preventing ROS from destroying its activity, as shown in Figure 2. In vivo experiments showed that this self-protecting hydrogel effectively promoted the repair of non-healing wounds in diabetes (Wu et al, 2019).…”
Section: Antioxidantmentioning
confidence: 98%
See 1 more Smart Citation
“…The design of this drug delivery system ensured that antagomiR-26a had direct contact with the ceria nanozymes, preventing ROS from destroying its activity, as shown in Figure 2. In vivo experiments showed that this self-protecting hydrogel effectively promoted the repair of non-healing wounds in diabetes (Wu et al, 2019).…”
Section: Antioxidantmentioning
confidence: 98%
“…It has been proven that biomaterials and bioactive agents with antioxidative function, including diol-citrate esters, edaravone, and cerium dioxide, can accelerate chronic wound healing (Luo et al, 2004;Zhu et al, 2016;Speidel et al, 2017;Fan et al, 2019;Wu et al, 2019).…”
Section: Antioxidantmentioning
confidence: 99%
“…Then, MSN-ceria attenuates oxidative stress at the site of the injury and prepares a friendly microenvironment for tissue regeneration. In these events, three factors play a lead role: firstly, nano-sized assembly facilitates the development of functional hybrid materials [ 147 ]; secondly, MSN shows a remarkable tissue adhesive capacity, which is required for rapid wound closure [ 148 , 149 ]; thirdly, the immobilization of CeO 2 nanocrystals prevents ROS from worsening with deleterious effects and potentiates the process of wound healing [ 150 ]. In this design, nanobridging for the recovery of barrier function is synergized with ROS-scavenging effects for control of the oxidative stress microenvironment, ultimately resulting in the substantial morphogenesis of skin appendages and the restricted formation of scar tissues.…”
Section: Figurementioning
confidence: 99%
“…Bio‐therapeutics are usually hindered by low stability in the oxidative microenvironment, resulting in suboptimal performance. [ 13‐17 ] Besides, high level of ROS can damage endogenous biomacromolecules, which will impair their functions that may be required for tissue regeneration. Hence, modulation of the oxidative microenvironment is a promising strategy to improve the efficacy of bio‐therapeutics and assist the intrinsic regeneration process.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7,23‐25 ] Particularly, ROS‐scavenging nanozymes, which are able to neutralize ROS and protect against oxidative damage, have shown significant promise for tissue repair and regeneration. [ 14,15,17,24,26‐37 ] For example, ceria nanocrystals and manganese dioxide nanoparticles have been found to have inherent catalase (CAT) and superoxide dismutase (SOD)‐mimetic activities, which can efficiently scavenge harmful ROS. [ 13,17,29‐31 ] Such antioxidant properties of ROS‐scavenging nanozymes can serve diverse purposes in regenerative medicine, such as protecting therapeutic nucleic acids, improving survival of stem cells, modulating the oxidative microenvironment, and assisting innate regeneration (Figure 1).…”
Section: Introductionmentioning
confidence: 99%